PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN ISAK 35 PADA YAYASAN AL-BARKAH PASIRJAMBU BANDUNG - Maulana Mukti, Muhammad Daud; Oon Feriyanto, oon (Universitas Muhammadiyah Bengkulu, 2024)
This research is motivated by issues related to the preparation of financial statements that do not yet comply with standards. A descriptive qualitative research method is used to compile the financial statements for the Al-Barkah Foundation, while descriptive analysis helps illustrate the issues based on actual conditions within the foundation. Data collection involved both primary and secondary sources, including field studies, interviews, documentation, and literature reviews. Based on the research findings, it was concluded that Al-Barkah Foundation’s financial statements currently consist of cash inflows from BOS funds and cash outflows for foundation activities. Therefore, the researcher has prepared financial statements for the foundation in accordance with ISAK 35. Keywords: Accounting, Foundation Financial Statements, ISAK 35